The Ideal Law State Concept in Indonesia; The Reality and The Solution - Juanda, Ogiandhafiz; Juanda (Journal of Law, Politic and Humanities, 2023)
The rule of law concept that has developed in Indonesia is a modern rule of law concept that has a distinctive feature compared to the concept of a rule of law state that developed before. However, in the development process, it is difficult to escape from the sparks of thinking about the concepts of "the rule of law" and "rechtsstaat". The ideal Indonesian legal state concept has the following characteristics: The administration of the state and government is always based on the values of Pancasila and the 1945 Constitution of the Republic of Indonesia. The state places the constitution, laws and statutory regulations as guidelines that must be obeyed in every life; The principle of legality is the main thing that must be guided by state and government administrators. Making law a means of realizing a welfare state and a democratic state; "The state recognizes and operates a power-sharing system and has checks and balances with each other." There is an independent and impartial judiciary that guarantees justice for everyone, including against abuse of authority by those in power; There is protection of Human Rights that is in balance with the obligations of Human Principles; The existence of democratic principles in the life of society, nation and state; There is a balance, harmony and harmony between rights and obligations; Recognition and realization of the principle of "good governance": realization of justice, order, legal certainty, benefit, welfare, and happiness for every citizen.